SOCIAL INTEGRATION AND CASTE IN INDIA: AN ANALYTICAL STUDY: Received: 06th April 2022; Revised: 31st May 2022, 06th Jun 2022, 24th June 2022; Accepted: 25th June 2022 - Kumar, Ajay (PEOPLE: International Journal of Social Sciences, 2022)
Indian society is known as multi-lingual, multi-religious, multi-castes, and multi-cultural in nature. Indian constitution gives equal rights to everyone regardless of gender, caste, class, community, language, and religious beliefs but it has been observed that caste plays an ascriptive role in Indian society since it divides society in a stratified manner which designates and promotes the hierarchical dogmatism and a sense of superiority to its lower caste. This creates discontent and disharmony in the society which becomes a crucial factor to nourish the disintegration in the society. The current study aimed to describe the impact of the divisive nature of caste on social integration in India. This empirical study included 216 respondents. The descriptive and explorative methodology was applied to achieve the results. To find out the principal factors that determine social disintegration due to caste impression in India, the data were analyzed by the SPSS version 26. The finding of the study provided that the divisive nature of the caste really hurts the societal integration power of India.